2022
DOI: 10.1002/smll.202202313
|View full text |Cite
|
Sign up to set email alerts
|

TiVCTx MXene/Chalcogenide Heterostructure‐Based High‐Performance Magnesium‐Ion Battery as Flexible Integrated Units

Abstract: Magnesium‐ion batteries (MIB) have gradually attracted attention owing to their high theoretical capacity, high safety, and low cost. A bimetallic metal–organic framework self‐sacrificing template and a co‐assembly strategy are used to prepare a high‐performance, stable cycling NiSe2‐CoSe2@TiVCTx (NCSe@TiVC) heterostructure MIB cathode that can be used as a flexible integrated unit to power future self‐powered systems. Benefiting from the synergistic effect of TiVCTx MXene and NCSe, the NCSe@TiVC heterostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Figure b elucidates the morphology of the as-synthesized DMPT immersed in 5 mg/mL MXene solution. It is worth noting that few MXene nanosheets were coated on the surface of the electrospun PLA nanofiber membrane . As the concentration of MXene increases, MXene nanosheets gradually penetrate and adhere onto the inner frame of electrospun PLA textiles, as shown in Figure c,d.…”
Section: Resultsmentioning
confidence: 94%
“…Figure b elucidates the morphology of the as-synthesized DMPT immersed in 5 mg/mL MXene solution. It is worth noting that few MXene nanosheets were coated on the surface of the electrospun PLA nanofiber membrane . As the concentration of MXene increases, MXene nanosheets gradually penetrate and adhere onto the inner frame of electrospun PLA textiles, as shown in Figure c,d.…”
Section: Resultsmentioning
confidence: 94%
“…Over the past several decades, the recording of physiological parameters of the human body using noninvasive methods has been the focus of research in the field of flexible wearable electronics. 1–7 Medical research results have shown that the high prevalence and mortality of cardiovascular and cerebrovascular diseases seriously threaten human health. 8–12 As many as 15 million patients die worldwide owing to cardiovascular diseases every year.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the human skin sensing system, researchers have developed a variety of flexible electronic skins that can mimic the sensing function of the human skin, bringing great convenience and development to people's activities and lives. [16][17][18][19][20] The conductive materials commonly used in flexible electronic sensors reported so far include carbon nanotubes (CNTs), 21,22 carbon black (CB), 23 graphene, 24 reduced graphene (RGO), 25 silver nanowires, 26,27 two-dimensional titanium carbide (MXene) 28,29 and conducting polymers. [30][31][32] To ensure the technical indicators of flexible electronic devices, e.g., transparency, flexibility and tensile strength, the following make excellent substrate materials: polydimethylsiloxane (PDMS), 33,34 thermal polyurethane (TPU), 35 sponge composites, 36,37 natural rubber (NR), 38,39 Ecoflex (overlapped CNT bundles coupled with a silicone elastomer) 40 and fiber materials.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the human skin sensing system, researchers have developed a variety of flexible electronic skins that can mimic the sensing function of the human skin, bringing great convenience and development to people's activities and lives. 16–20 The conductive materials commonly used in flexible electronic sensors reported so far include carbon nanotubes (CNTs), 21,22 carbon black (CB), 23 graphene, 24 reduced graphene (RGO), 25 silver nanowires, 26,27 two-dimensional titanium carbide (MXene) 28,29 and conducting polymers. 30–32 To ensure the technical indicators of flexible electronic devices, e.g.…”
Section: Introductionmentioning
confidence: 99%